Comportamiento organizacional y su influencia en el desempeño laboral en la Cooperativa de Ahorro y Crédito ‘‘COACMES’’ - Villacis Ponce, Luis Ricardo (2023)
The research was developed with the objective of evaluating the variables of organizational behavior and its influence on job performance in the "COACMES" Savings and Credit Cooperative in San Jacinto city, which was developed under a bibliographic, descriptive approach and field. The preparation of the study consisted of 4 stages: (1) the indicators of the study variables were identified through a bibliographic review, which were validated by the Delphi method, and selected with the use of the Kendall consensus technique; (2) Subsequently, the current state of the variables was measured through the application of an Ad Hoc structured survey, with Likert scale response options, giving way to data processing in the SPSS software, in which it was calculated Cronbach's Alpha; (3) from the results obtained, the relationship between the study variables and their indicators was determined with the application of the Pearson Test; (4) Finally, an improvement plan was prepared using the 5w+1h matrix, counting as the main input, the analysis of the problems to be solved. The results determined that there is a non-significant moderate positive influence between organizational behavior and work performance, which is why it is concluded that the cooperative must apply improvement mechanisms that contribute to potentiate the current incidence, and in this way apply better internal management.